EP841 Bilateral ovarian solid tumors in young female with autosomal dominant inherited genetic syndrome. (1st November 2019) - Ferreira Rangel Neto, O; Lessa, LF; Bertoletto, CDCR; Pereira, MA; Nicolau, SM; Uyeda, MGK
Abstract : Introduction/Background: Gorlin-Goltz syndrome is an autosomal dominant inherited disorder characterized by the presentantion of tumors in different sites, particularly the skin. Due to the manifestation of recurrent cutaneous tumors, the syndrome is also known as Nevoid Basal Cell Carcinoma Syndrome. Methodology: This is a case of a woman with Gorlin-Goltz syndrome with bilateral adnexal tumors. Results: A 28-year-old female from the northeastern region of Brazil, with a history of more than 15 surgical procedures for excision of cutaneous tumors, referred to division of gynecological oncology by bilateral pelvic mass of possible adnexal origin, with antecedent of a son who underwent surgical removal of medulloblastoma at the age of four years. Clinical examination revealed solid, mobile and lobulated mass of 12 cm on right adnexal topography and another 4 cm on the left. In addition, the imaging exam revealed fusion of the fourth and fifth ribs in the right. Negative tumor markers. A laparotomy was performed and revealed solid ovarian masses, with regular limits, 15 cm in the Right and 4 cm in the left, performed bilateral salpingo-oophorectomy. Histopathological analysis revealed multinodular fibroma with dystrophic calcification. Conclusion: Ovarian Fibroma are benign neoplasm, infrequent, with incidence of 4% in the general population. Patients with ovarian fibroma are usually referred to the oncologic gynecologist for present a solid and expansive mass, that may be associated with ascite and pleural effusion (Meigs Syndrome), being an important differential diagnosis of malignant ovarian tumors. Women with Gorlin-Goltz Syndrome may be present ovarian fibroma in up to 25% of cases. The main clinical manifestation of this genetic syndrome is cutaneous basal cell carcinomas. Other findings are skeletal changes in 70% of cases (bifid ribs, fused and widened ribs), odontogenic tumors usually in the first decade of life, neurological changes are rare and include medulloblastoma more frequently. Disclosure: Nothing to disclose.